Hot fox: ladybird reading phonics book 3 - Crossley, Dick; King, Sue (Ladybird Italy, 2022)
"Hot Fox" by Ladybird is a playful and engaging story about a clever fox who uses his wit to navigate various situations. The narrative follows the fox as he encounters challenges in the wild, showcasing his resourcefulness and charm. Through lively illustrations and rhythmic text, the story captures the attention of young readers, emphasizing themes of cleverness, problem-solving, and the beauty of nature. It's a fun and entertaining read that encourages imagination and exploration.